Political memes in the 2018 presidential campaigns in Russia: Dialogue and conflict. Issue 1 (1st June 2019) - Lukianova, Natalia; Shteynman, Maria; Fell, Elena
The authors seek to contribute to the existing discussion of the communicative function of political memes by bringing into discussion political memes used by opposition leaders in the 2018 Russian presidential election campaigns as examples of memes being purposefully deployed in targeted political communications. Specifically, they focus on Navalny's use of the 'yellow duck' meme. Drawing on the existing research of memes' mythological properties, the authors claim that the combination of dialogue and conflict as two main functions entailed in the political meme is a likely key element that increases the popularity of a meme and makes it viral. The discussion of concrete examples is preceded by a discussion that contextualizes the study of a political meme within the field of communication studies as a device that offers clarity in the chaotic flow of information, is constructed by both addresser and the addressee and serves as an effective tool for promoting ideologies.